The use of genome sequencing to investigate an outbreak of hospital‐acquired mucormycosis in transplant patients. Issue 5 (13th September 2019) - Marek, Caitlyn; Croxen, Matthew A.; Dingle, Tanis C.; Bharat, Amrita; Schwartz, Ilan S.; Wiens, Rhoda; Smith, Stephanie
Abstract: We report three cases of hospital‐acquired mucormycosis in heart and lung transplant patients over a 6‐month period. Traditional epidemiological investigation tools were used to look for a common link between patients to explain the outbreak. Genome sequencing of each fungal strain was used to supplement the investigation. By disproving a close genetic link between infecting strains of mucormycosis, we were able to conclude the outbreak investigation. Genome sequencing is a novel tool that can be used in addition to traditional epidemiologic investigations to help determine linkage of patients during outbreak investigations.